Endoplasmic Reticulum Unfolded Protein Response, Aging and Exercise: An Update - Estébanez, Brisamar; de Paz, José A.; Cuevas, María J.; González-Gallego, Javier (Frontiers in physiology, 2018)
The endoplasmic reticulum (ER) is a dynamic and multifunctional organelle responsible for protein biosynthesis, folding, assembly and modifications. Loss of protein folding regulation, which leads to unfolded or misfolded proteins accumulation inside the ER lumen, drives ER stress (ERS) and unfolded protein response (UPR) activation. During aging, there is a decline in the ability of the cell to handle protein folding, accumulation and aggregation, and the function of UPR is compromised. There is a progressive failure of the chaperoning systems and a decline in many of its components, so that the UPR activation cannot rescue the ERS. Physical activity has been proposed as a powerful tool against aged-related diseases, which are linked to ERS. Interventional studies have demonstrated that regular exercise is able to decrease oxidative stress and inflammation and reverse mitochondrial and ER dysfunctions. Exercise-induced metabolic stress could activate the UPR since muscle contraction is directly involved in its activation, mediating exercise-induced adaptation responses. In fact, regular moderate-intensity exercise-induced ERS acts as a protective mechanism against current and future stressors. However, biological responses vary according to exercise intensity and therefore induce different degrees of ERS and UPR activation. This article reviews the effects of aging and exercise on ERS and UPR, also analyzing possible changes induced by different types of exercise in elderly subjects.